2020
DOI: 10.2147/ott.s239398
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resistance Mechanism of PD-1/PD-L1 Blockade in the Cancer-Immunity Cycle</p>

Abstract: In recent years, the PD-1/PD-L1 axis blockade has become a very promising therapy with significant clinical benefits for multiple tumor types. However, some patients still do not respond sufficiently to PD-1/PD-L1 targeted monotherapy. Therefore, investigating the mechanism of PD-1 blockade resistance will assist in exploring new immunotherapy strategies, controlling the progress of the disease, and thus bringing more sustainable survival benefits to patients. The tumor-immune cycle is divided into the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 98 publications
0
22
0
Order By: Relevance
“…A large number of basic and clinical experiments are currently underway, including allogeneic stem cell transplantation, antitumor vaccines, proinflammatory cytokines, chimeric antigen receptors, and adoptive T cell metastasis. One of the most promising methods considered is ICT (Yu et al, 2018;Zhu et al, 2019;Zhuang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of basic and clinical experiments are currently underway, including allogeneic stem cell transplantation, antitumor vaccines, proinflammatory cytokines, chimeric antigen receptors, and adoptive T cell metastasis. One of the most promising methods considered is ICT (Yu et al, 2018;Zhu et al, 2019;Zhuang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, considerable challenges, such as lack of durable remission, low response rate, drug resistance and immunerelated adverse effects, still remain to be addressed. [5][6][7][8][9][10] It is generally considered that PD-L1 expressed on the tumor cell surface is upregulated in the tumor microenvironment to activate PD-1 on CD8 T cells, delivering the co-inhibitory signals and thereby suppressing T cell function. 11 However, except being presented on the tumor cell surface, PD-L1 is also dynamically circulating inside tumor cells 12 13 as well as excreted into extracellular space via the exosomes, 14 15 contributing to the resistance to anti-PD-L1 antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, their number, distribution, phenotype, and function can change as the tumor progresses. Studies have shown that the number of DCs in peripheral blood of patients with head and neck squamous carcinoma is different from that of healthy individuals [ 159 ]. In a model of spontaneous ovarian cancer, Scarlett and colleagues observed a functional switch in DCs from an immunostimulatory to an immunosuppressive phenotype.…”
Section: Dendritic Cells and Cross-presentation In Cancermentioning
confidence: 99%